Difference in the deactivation of Au catalysts during ethanol transformation when supported on ZnO and on TiO2. Issue 14 (15th February 2018) - Morales, M. V.; Asedegbega-Nieto, E.; Castillejos-López, E.; Bachiller-Baeza, B.; Guerrero-Ruiz, A.
Abstract : Au NPs of different sizes were supported on two metal oxides: ZnO and TiO2 . Differences in ethanol transformation for Au of similar particle size reveal that TiO2 support induces condensation products while ZnO only gives place to dehydrogenation. Abstract : Au nanoparticles of different sizes were supported by the deposition–precipitation method on two metal oxides: ZnO and TiO2 . The resulting catalysts were tested in the ethanol catalytic transformation reaction. Both metal oxide support materials exerted a different influence on the achieved Au particle size as well as on the behavior of the subsequent catalyst, with regard to their initial conversion values, product distribution and stability. While TiO2 favors the formation of smaller nanoparticles, ZnO offers larger Au particle sizes when prepared under similar conditions. At the same time, TiO2 produced catalysts which displayed higher initial conversions in comparison with AuZnO catalysts, even when observing catalysts of each series with similar particle sizes. At the same time, catalysts supported on ZnO exhibited higher resistance to deactivation caused by coke formation. These results were evidenced employing different characterization techniques on both used and fresh catalyst samples. The decline in deactivation was generally accompanied by an increase in the carbon content on the catalyst's surface.